Exploring Figurative Language in Rupi Kaur’s Selected Poems - Heda, Ayuni; Bram, Barli (Al-Lisan: Jurnal Bahasa, 2021)
This study explored figurative language or figures of speech used in the seven poems entitled Home, Time, Self-love, Self-hate, The Construction Site of Our Future, Long-distance, and It Is So Full Here in Myself by Rupi Kaur. The researchers used a descriptive qualitative method. Library research was used as the technique in collecting the data. The data were collected from Kaur’s poem book entitled The Sun and Her Flowers and analysed using the figurative language or figures of speech proposed by Abrams and Harpham (2015). Results showed four types of figurative language used in Kaur’s selected poems: personification, nine instances; simile, six occurrences; hyperbole, six occurrences; and metaphor, three examples